Persistence of Antibodies Against Spike Glycoprotein of SARS-CoV-2 in Healthcare Workers Post Double Dose of BBV-152 and AZD1222 Vaccines - Choudhary, Hari Ram; Parai, Debaprasad; Chandra Dash, Girish; Kshatri, Jaya Singh; Mishra, Narayan; Choudhary, Prasanta Kumar; Pattnaik, Dipti; Panigrahi, Kumudini; Behera, Susmita; Ranjan Sahoo, Nihar; Podder, Sreeparna; Mishra, Adyasha; et al. (Frontiers in Medicine, 2021)
Purpose: We investigated the persistence of the vaccine-induced IgG antibodies against SARS-CoV-2 among health care workers in Odisha who received complete dose of either Covaxin or Covishield vaccine. Methods: This 24-week longitudinal cohort study was conducted from January to July 2021 with participants from six healthcare and research facilities of Odisha to understand the dynamicity of the vaccine-induced IgG antibodies against SARS-CoV-2, after the complete dose of vaccines. Results: Serum samples were collected from 614 participants during each follow-up and were tested in two CLIA-based platforms to detect SARS-CoV-2 antibodies both qualitatively and quantitatively. Among these participants, 308 (50.2%) were Covishield recipients and the rest 306 (49.8%) took Covaxin. A total of 81 breakthrough cases were recorded and the rest 533 heath care workers without any history of post-vaccination infection showed significant antibody waning either from T3 (Covaxin recipient) or T4 (Covishield recipient). The production of vaccine-induced IgG antibodies is significantly higher (p<0.001) in Covishield compared to Covaxin. Covishield recipients produced higher median anti-S IgG titre than Covaxin. No statistically significant differences in antibody titres were observed based on age, gender, comorbidities and blood groups. Conclusion: This six-month follow-up study documents a two-fold and four-fold decrease in spike antibody titre among Covishield and Covaxin recipients, respectively. The clinical implications of antibody waning after vaccination are not well understood. It also highlights the need for further data to understand the longterm persistence of vaccine-induced antibody and threshold antibody titre required for protection against reinfection.